Competition and conjugation between agrobacterial cooperators and cheaters - Guzman, Priscila Amanda (Kansas State University, 2022)
Natural selection favors selfish behaviors that undermine the stability of cooperative systems. Despite this, cooperation is widespread throughout nature, including in the microbial world. This dissertation examines the interactions between bacterial cheaters and cooperators, and how these interactions influence the evolution of cooperation and virulence. Bacterial cooperators often pay a fitness cost to provide a benefit, a public good, that benefits the cooperator and other nearby individuals. These public goods drive the emergence of cheaters, individuals that do not pay the costs of cooperation but do benefit from the public goods produced by cooperators. Because cheaters have an inherent competitive advantage over cooperators, they threaten the stability of cooperative systems. Cooperative individuals may employ strategies that antagonize cheaters, thereby preventing cheaters from spreading through the population. In Agrobacterium tumefaciens, a plant pathogen and the causative agent of crown gall disease, cooperation is a key feature of its infection of host plants. Cooperative agrobacteria carry the tumor inducing (Ti) plasmid that encodes the virulence genes required for the genetic transformation of plants. The act of infecting the plants is metabolically costly, involving the expression of the vir genes required to form a type IV secretion system and the effectors that mediate delivery of the T-DNA (transferred DNA) into the plant’s genome. This genetic transformation of the plant by the T-DNA results in the misregulation of plant hormones and the production of opines, small compounds that serve as a nutrient source for agrobacteria. Cheater agrobacteria, individuals that do not infect plants, but do catabolize opines, replicate faster than their cooperative counterparts. Yet, despite this expected competitive advantage, natural cheaters have not been observed dominating the agrobacterial populations associated with natural galls. My research focuses on three main areas related to the interaction between agrobacterial cooperators and cheaters: the population ecology of cheaters, conjugation of the Ti plasmid into cheaters, and screening platforms for the study of competitive interactions between cheaters and cooperators. Broadly, I demonstrated that ΔvirA mutants are cheaters that have a large fitness advantage over virulent agrobacteria. Further, I showed that in gall-like environments the expression of virulence is very costly for agrobacterial cooperators. As a result, agrobacterial cheaters readily arise de novo in these environments. I explored the antagonistic interactions between cheaters and cooperators, focusing on whether pathogenic agrobacteria used horizontal gene transfer as a policing mechanism to prevent cheaters from taking over. In A. tumefaciens, conjugation is regulated in response to bacterial cell density by quorum sensing (QS). To understand the effects of conjugation on cheater policing, I carried out competitions involving mutants lacking TraR. I found that TraR is necessary for conjugation and that traR+ cooperators compete more favorably against ΔvirA cheaters than do traR- cooperators. However, conjugation alone will not antagonize cheater spread when they are already present in a population. In contrast, when cheaters arise via de novo mutations, conjugation can serve as a policing mechanism against freeloaders. Finally, driven by the limitations of current platforms for the screening of microbial interactions, I collaborated on the development of a new tool for the screening of microbial interactions. I used a photodegradable hydrogel that allows for high-throughput screening of bacterial populations in just one experimental trial. As a proof-of-principle, I studied a known interaction between an agrobacterial cooperator and a cheater and demonstrated that our approach allows the screening of entire transposon mutant libraries in a single experiment. In a first screen of this kind, I was able to identify, extract, and characterize rare cells (9/28,000) using this high-throughput approach. Thus, photodegradable hydrogels offer a powerful, straightforward, and adaptable approach that can be used not only for the screening of cheater-cooperator competitive interactions, but also more broadly for the study of other microbial interactions.
Keywords: Agrobacterium tumefaciens; Horizontal gene transfer; Evolution of cooperation; Bacterial cheaters; Microbial interactions